Construct Validity of the Sensory Profile Interoception Scale: Measuring Sensory Processing in Everyday Life - Dunn, Winnie; Brown, Catana; Breitmeyer, Angela; Salwei, Ashley (Frontiers in Psychology, 2022)
Scholars and providers are coming to realize that one’s ability to notice and respond to internal body sensations (i.e., interoception) contributes to an overall sense of wellbeing. Research has demonstrated a relationship between low interoceptive awareness and anxiety, for example Currently, however, tools for evaluating one’s interoception lack the conceptual foundation and clarity necessary to identify everyday behaviors that specifically reflect interoceptive awareness. Unlike existing interoceptive measures, the Sensory Profile Interoception (SPI) scale is participation-based and grounded in Dunn’s Sensory Processing framework. In this study we investigated construct validity by correlating the SPI with related measures: the Adolescent/Adult Sensory Profile (A/ASP), the Perth Alexithymia Scale (PAS), the Body Awareness Scale (BAS), and the State-Trait Anxiety Inventory (STAI). Using the REDCAP online platform, 74 college-aged participants completed the measures. Using Pearson product-moment correlations there were statistically significant relationships between the corresponding sensory pattern subscales on SPI and A/ASP (r = 0.311 to r = 0.605). The PAS was only weakly related to the registration subscale of the SPI (r=0.261). The BAS had significant relationships with seeking and avoiding on the SPI (r=0.465 and r=0.394). The STAI had significant relationships with sensitivity and registrations of the SPI (r=0.374 and r=0.307 for state; r=0.445 and r=0.350 for trait). Taken together, these findings provide evidence of construct validity of the SPI to identify participation patterns associated with both high and low interoception. With the more precise information the SPI provides, professionals can design tailored interventions to support everyday life goals and researchers can study interoception within authentic activities.